Bioethanol from Pineapple Peel with Variation of Saccharomyces Cerevisiae Mass and Fermentation Time - Eka Sri Yusmartini; Mardwita Mardwita; Junanda Marza (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The avaibility of energy from fossil fuel is gradually decreasing. The solution to overcome this problem is to develop an alternative energy source that can be renewed such as bioethanol. Bioethanol is a vegetable based fuel, an alternative energy that can be used as a subtitute for petroleum. One of the raw materials that can be used for the fermentation of bioethanol production is pineapple fruit skin. This research aims to utilize pineapple fruit waste as raw material for making bioetanol by fermentation process, with variations in the addition of saccharomyces cereviceae 20, 25 and 30 g, and time fermentation 5 and 9 days. The highest levels of bioethanol obtained 6,83 % at the addition of 25 g saccaromces cereviceae and fermentation time of 5 days. Keywords: pineapple skin, saccaromyces cereviceae, fermentation, bioethanol